2017
DOI: 10.1097/md.0000000000007883
|View full text |Cite
|
Sign up to set email alerts
|

The cost-saving effect and prevention of medication errors by clinical pharmacist intervention in a nephrology unit

Abstract: Medication errors may lead to adverse drug events (ADEs), which endangers patient safety and increases healthcare-related costs. The on-ward deployment of clinical pharmacists has been shown to reduce preventable ADEs, and save costs. The purpose of this study was to evaluate the ADEs prevention and cost-saving effects by clinical pharmacist deployment in a nephrology ward.This was a retrospective study, which compared the number of pharmacist interventions 1 year before and after a clinical pharmacist was dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 21 publications
2
49
1
1
Order By: Relevance
“…The general administration of pharmaceutical care underway pharmacy practice as part of pharmacy strategic plan in Saudi Arabia. The previously study by Chen C et al 14 The predictable cost saving was calculated conventionally by a 1 day cost of the intervened medications. Moreover, the estimated cost avoidance was also calculated orthodoxly based on only 2 extra days of admission if ADEs occurred, although this may have resulted in more than 2 days of admission according to the Chen C et al 11 Other study by Najafzadeh M et al found contrasted from our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general administration of pharmaceutical care underway pharmacy practice as part of pharmacy strategic plan in Saudi Arabia. The previously study by Chen C et al 14 The predictable cost saving was calculated conventionally by a 1 day cost of the intervened medications. Moreover, the estimated cost avoidance was also calculated orthodoxly based on only 2 extra days of admission if ADEs occurred, although this may have resulted in more than 2 days of admission according to the Chen C et al 11 Other study by Najafzadeh M et al found contrasted from our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, Chen CC et al revealed that the benefit/cost ratio increased from 4.29 to 9.36 and average admission days decreased by 2 days after the on-ward deployment of a clinical pharmacist. 14 In addition, the total cost avoidance was 103,073,160 -224,590,140 US $ annually. Another study by Najafzadeh M et al found 52% reduced of medication reconciliation discrepancies and total saved was 175,306 US $ in the study period.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have associated prescription errors with extra expenses accrued for institutions or health systems. 5,7,16 In view of the method used in this study, and the hesitation of some participants to report the amount of money spent, it was impossible to quantify their financial loss. However, based on the report of 19 (59.4%) participants, it was demonstrated that prescribing errors are also source for unnecessary expenditure because the medicines were not dispensed.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Studying medication errors and their causes has been an important tool to identify opportunities for the improvement of the medication process, with a consequent reduction in the risks and costs associated with these adverse events. 7 However, this information has evidently not been sufficient to convince health managers and prescribers to invest in changes that can reduce prescribing errors. Therefore, although prescribing errors have been widely studied, misadventures experienced by patients due these errors are neglected by healthcare professionals, especially in the cases of low-income patients covered by public health systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation